Review on Eurycoma longifolia Pharmacological and Phytochemical Properties - Aini Norhidayah, Mohamed; Jaya Vejayan, Palliah; M. M., Yusoff (Asian Network for Scientific Information, 2015)
Eurycoma longifolia or Tongkat Ali is famous for its aphrodisiac property and the traditional uses range from tonic after childbirth to treating malaria. Phytochemical studies revealed the presence of bioactive compounds such as quassinoids, alkaloids, squalene derivatives, tirucallane-type triterpenes and biphenylneolignans. Existing research revealed that plant has potential to treat various diseases and to replace the current treatment. Purpose of this article is to evaluate and summarize the existing literatures concerning phytochemical, biological and toxicological studies of E. longifolia. It is expected that critical evaluation will be useful for researchers working on